Optimizing Health Protocol Enforcement during the Covid-19 Pandemic - Julista Mustamu; Andress D Bakarbessy (LAW REFORM, 2020)
The effort of the prevention and countermeasures in order to break the chain of transmission of Corona Virus Disease 2019 (Covid-19), it needs to be done in an integrated and comprehensive manner from various aspects of governance, health, socio-cultural and economic aspects. As part of the state of public health emergencies and has beeb designated as a non natural disaster, the regional goverment has the authority to take preventive and countermeasures actions primarily in the enforcement of health protocol during the Covid-19 pandemic in accordance with statutory provinsions. The research objective is to understand the enforcement of health protocols during the Covid-19 pandemic. The research method used is juridical-normative with a statutory approach and a conceptual approach to analyze problems qualitatively. The results and discussion concluded that The formulation of policies and formation of regional legal product that from the basic of legitimacy as well as the basic of legality to act for local goverments in the efoort to optimize the enforcement of prtococols during the Covid-19 pandemic, certaily need to develop specific policy formulation models and becemo a reference for local goverments in policy formulations and formulation reginal legal product in the enforcement of the Covid-19 health protocol. Policy formulation and formation of regional legal product in the enforcement of the Covid-19 health protocol include, and a review of the stages of policy formulation